Protein‐Framed Multi‐Porphyrin Micelles for a Hybrid Natural–Artificial Light‐Harvesting Nanosystem. Issue 28 (17th May 2016) - Liu, Yannan; Jin, Jiyang; Deng, Hongping; Li, Ke; Zheng, Yongli; Yu, Chunyang; Zhou, Yongfeng
Abstract: A micelle‐like hybrid natural–artificial light‐harvesting nanosystem was prepared through protein‐framed electrostatic self‐assembly of phycocyanin and a four‐armed porphyrin star polymer. The nanosystem has a special structure of pomegranate‐like unimolecular micelle aggregate with one phycocyanin acceptor in the center and multiple porphyrin donors in the shell. It can inhibit donor self‐quenching effectively and display efficient transfer of excitation energy (about 80.1 %) in water. Furthermore, the number of donors contributing to a single acceptor could reach as high as about 179 in this nanosystem. Abstract : Nanopomegranate : A micellar light‐harvesting nanosystem was prepared consisting of one phycocyanin protein acceptor in the core and many porphyrin donors packed in a pomegranate‐like manner in the shell. The system inhibited donor self‐quenching effectively and displayed efficient transfer of excitation energy in water.